(untitled) (Ágora Journal, 2024)
This article intends to demonstrate the diversity of proposals and ideas existing in the Ceará modernist movement in the beginning of the 20th century, based on the responses of some intellectuals participating in the literary poll published in the newspaper O Povo, in 1929. We understand that every historical experience is unique and unrepeatable and that is why we must understand the modernist movements in their particularities and diversities, without falling into false evaluative dilemmas that define an ideal model to which every concrete experience should fit. With this we aim to present the richness and diversity of Modernisms that took place in Brazilian cities in the 1920s, specifically the case of the modernist experience in Ceará.